Safety and Efficacy of Lidocaine with Adrenaline for Ring Block Anesthesia in Finger Surgeries (Medical Forum Monthly, 2024)
Objective: To determine the safety and efficacy of Lidocaine (Xylocaine) with adrenaline (1:100,000) for ring block anesthesia in finger surgeries.Study Design: Descriptive case series study.Place and Duration of Study: This study was conducted at the Plastic Surgery Unit, Liaquat National Hospital, Karachi from October 17, 2015 to April 16, 2016.Materials and Methods: All 18- 60 years patients of either gender with post traumatic injuries to fingers with duration of trauma <1 week or elective surgeries of fingers with presence of pathology less than 1 year were enrolled. Patients received lidocaine 1% with 1:100,000 epinephrine on the finger/fingers to be operated. Efficacy and safety of anesthetic combination was noted.Results: Mean age of the patients was 32.93±11.17 years. Mean time since trauma was 62.64±99.73 days. Male preponderance was found to be higher. Type of injury was RTA in 17 (26.2%) patients, door entrapment 11 (16.9%), machine 11 (16.9%) and other injuries in 26 (40%) of the patients. Safety was observed in all 65 (100%) patients whereas efficacy was observed in 60 (92.3%) fingers of the patients.Conclusion: Safety and efficacy of Lidocaine with adrenaline was found satisfactory for ring block anesthesia in finger surgeries.